High culture and tall chimneys : art institutions and urban society in Lancashire, 1780-1914 - Moore, James (Manchester University Press, 2018)
This new study examines how nineteenth-century industrial Lancashire became a leading national and international art centre. By the end of the century almost every major town possessed an art gallery, while Lancashire art schools and artists were recognised at home and abroad. The book documents the remarkable rise of visual art across the county, along with the rise of the commercial and professional classes who supported it. It examines how Lancashire looked to great civilisations of the past for inspiration while also embracing new industrial technologies and distinctively modern art movements. This volume will be essential reading for all those with an interest in the new industrial society of the nineteenth century, from art lovers and collectors to urban and social historians